Comparison of shallow basement thermal performance for different regions of Morocco using a three-dimensional heat transfer analysis. Issue 1 (1st January 2019) - Sakami, Naima; Boukhattem, Lahcen; Hamdi, Hassan; Benhamou, Brahim
Abstract: A three-dimensional numerical model was built to estimate the heat transfer between the soil and a shallow basement in four different climates (cold, temperate, semi-arid and arid climates) for, respectively, conditioned and unconditioned cases. The governing heat transfer equation in soil and basement was solved by the finite difference method using the alternating-direction implicit scheme (ADI). The air temperature for the case of conditioned shallow basement was maintained constant while it was computed for the case of unconditioned cellar using energy balance equation. The effects of the basement geometry, soil types and climatic conditions on the thermal behavior of the conditioned and unconditioned shallow basement were carried out. The heat losses and isotherms analysis showed that the heat flux is more significant through the walls than the basement floor and occurred mainly in the walls-floor edges. Furthermore, lowering the thermal diffusivity of the soil leads to a decrease in the shallow basement heating load. Our results show that the shallow basement as expected is more beneficial in hot climates than in cold ones. It was also brought to light that the basement thermal load is dependent on the soil type in temperate climates.